The rise of women and their impact on firms' performance. (2016) - Salloum, Charbel; Azzi, Georges; Mercier-Suissa, Catherine; Khalil, Stephanie
This paper aims to understand how the presence of women in management positively affects firms' financial performance. In order to validate our hypotheses, we used a quantitative method to collect data and performed an inquiry by surveying the top 30 Lebanese firms. The results showed that the presence of women in management in Lebanon is not positively correlated with firms financial performance. Women occupying high managerial positions are most probably a member of the family owning the business, and therefore they are not directly concerned with the management of the business. Moreover, a large number of the surveyed females in our sample are married. Consequently, their priorities change, and they put their family before their career development.